Overexpression of a DEAD box helicase Psp68 gene and its mutant confers salinity stress tolerance in bacteria (Bangladesh Journal of Agriculture, 2023)
Salinity stress adversely affects crop plant growth and productivity resulting in significant yield losses worldwide. Hence, it is essential to develop stress-tolerant species and as well as to understand the mechanisms behind it. The Psp68 is a DNA and RNA helicase and it is involved in numerous processes including protein synthesis, maintaining the basic activities of the cell, transcriptional activation/repressors, RNA processing, and abiotic stress response. This study evidence that overexpression of Psp68 provides salinity (NaCl and LiCl) stress tolerance in bacteria Escherichia coli bacterium also. Furthermore, the site-directed mutagenesis technique was applied to create three single mutants namely K168A, Q286G and R461Q, and their expression was also checked in response to the above mentioned stresses. Surprisingly, only the overexpression of single mutant R461Q showed high salinity stress tolerance in E. coli. Therefore, this study provides a new tool for developing stress tolerant crop plants and bacteria of agronomic importance in the field of agricultural biotechnology.Bangladesh J. Agri. 2022, 47(2): 17-26